2002
DOI: 10.1007/s004080000089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body-Weight Components on Forced Spirometry in Healthy Italians

Abstract: Many studies have investigated lung function in relation to age and height among Caucasians, however, most of these studies did not consider the individual components of body weight. The objective of the present study was to study the effect of body weight components [bone-free lean body mass (BF-LBM), bone mineral content (BMC), and fat mass (FM)] measured by dual x-ray absorptiometry (DXA) on the lung-function variables (FVC, FEV1, and PEF) and to derive prediction equations for these variables in healthy ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Various studies have shown altered pulmonary function in individuals with class III obesity. However, there have been few studies involving obese individuals with lower BMI (29,31,33) . In 1978, Schoenberg et al (29) reported that, due to the related increase in muscle strength, pulmonary function initially increases in parallel with weight gain, although subsequent impairment of chest wall mobility results in reduced pulmonary function.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown altered pulmonary function in individuals with class III obesity. However, there have been few studies involving obese individuals with lower BMI (29,31,33) . In 1978, Schoenberg et al (29) reported that, due to the related increase in muscle strength, pulmonary function initially increases in parallel with weight gain, although subsequent impairment of chest wall mobility results in reduced pulmonary function.…”
Section: Resultsmentioning
confidence: 99%
“…23 The largest FVC and FEV 1 values were recorded after examining the data from all the acceptable curves, even if they did not come from the same curve. [24][25][26] …”
Section: Lung Functionmentioning
confidence: 99%
“…The spirometric parameters most commonly employed are forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1). The prediction of FVC and FEV1 from equations based on gender, age and height is commonly employed to obtain reference values for evaluating lung function (Parma et al 1996;Coultas et al 1998;Mohamed et al 2002). Other anthropometric parameters such as body mass index (BMI) may slightly improve the accuracy of the prediction (Marcus et al 1988).…”
Section: Introductionmentioning
confidence: 99%